Landslide Disaster Hazard Analysis On Built-Up Areas In Banyubiru Sub-District Semarang Regency Using Geographic Information System - Putri, Alifa Salsabilla; Awaluddin, Moehammad; Sasmito, Bandi (Jambura Geoscience Review, 2024)
Banyubiru Sub-District is the sub-district that experienced the most landslides in Semarang Regency. The condition of steep slopes in several areas in this sub-district is quite dangerous to be used as a residential, industrial and commercial area because of the high probability of disasters, especially landslides. This research focuses on identifying landslide hazard areas, especially on built-up areas in Banyubiru Sub-District, Semarang Regency. The production of landslide hazard map refers to Peraturan Menteri Pekerjaan Umum Nomor 22/PRT/M/2007. The method used to identify landslide hazard areas is scoring and weighting using several parameters, namely slope, land cover, rock type, rainfall and soil type. Based on the processing, it can be known that mapping using the average monthly rainfall parameter for three months is more accurate than using annual rainfall. Landslide hazard on built-up areas in Banyubiru Sub-district is divided into three levels with the dominance of medium landslide hazard level covering 69% or approximately 275.70 Ha. The validation results show that out of 55 landslide events in Banyubiru Sub-district, 17 events occurred on built-up areas with medium to high hazard levels.